Effectiveness of road safety prevention in schools - von Beesten, Silke; Bresges, André (Frontiers in Psychology, 2022)
The World Health Organization estimates that each year 1.3 million people are killed and more than 50 million people worldwide, are injured in road traffic accidents. According to a study conducted by the Allianz Center for Technology, more young people between the ages of 15 and 29 die in traffic accidents than as a result of illness, drugs, suicide, violence or war events worldwide. That's about 400,000 per year, globally. Worldwide traffic accident prevention campaigns demonstrate the consequences of traffic accidents in an emotionalizing way in order to encourage drivers to adopt conscious safety behavior via adequate driving behavior. The Consequences of traffic accidents are demonstrated by prevention camapigns often in an emotionalizing way to encourage drivers to adopt safety measurements through adequate driving behavior. Prior research suggests that the emotionalizing effect of the appeals must be accompanied by solution- as well as action-oriented and self-confidence-increasing measures so that the instructive message is reinforced an does not lead to reactance. Thus, a strong need arose in the schools for a targeted training as follow-up of emotional prevention campaigns. A suitable training for knowledge acquisition and knowledge transfer into everyday life was developed by means of the Design-Based-Research method. To create the targeted follow-up, various methods from cognitive behavioral therapy and common traffic safety programs were adapted. This publication is dedicated to a first explorative research approach in a non-standardized form of a social training. It approaches the question of negative emotional states immediately after a stage event that confronts with real accidents. Changes in social behavior and development of participants' own norms, values, and attitudes were observed and documented and are discussed and presented in this article. The result of the survey confirmed prior research and showed visible effects of reactance after the Crash Curs NRW Campaign. It was found that a structured follow-up training is suitable to gain reactive behavior from the stage event. Knowledge deficits about the cause and outcome of accidents were successfully adressed in the follow up. This may have influence the reactance behaviour and could be a key factor for successful prevention campaigns.